Traumatic stress symptoms among Spanish healthcare workers during the COVID-19 pandemic: a prospective study - Portillo-Van Diest, Ana; Vilagut, Gemma; Alayo, Itxaso; Ferrer, Montse; Amigo, Franco; Amann, Benedikt L.; Aragón-Peña, Andrés; Aragonès, Enric; Asúnsolo Del Barco, Ángel; Campos, Mireia; Del Cura-González, Isabel; Espuga, Meritxell; et al. (Epidemiology and psychiatric sciences, 2023)
To investigate the occurrence of traumatic stress symptoms (TSS) among healthcare workers active during the COVID-19 pandemic and to obtain insight as to which pandemic-related stressful experiences are associated with onset and persistence of traumatic stress. This is a multicenter prospective cohort study. Spanish healthcare workers ( = 4,809) participated at an initial assessment (i.e., just after the first wave of the Spain COVID-19 pandemic) and at a 4-month follow-up assessment using web-based surveys. Logistic regression investigated associations of 19 pandemic-related stressful experiences across four domains (infection-related, work-related, health-related and financial) with TSS prevalence, incidence and persistence, including simulations of population attributable risk proportions (PARP). Thirty-day TSS prevalence at T1 was 22.1%. Four-month incidence and persistence were 11.6% and 54.2%, respectively. Auxiliary nurses had highest rates of TSS prevalence (35.1%) and incidence (16.1%). All 19 pandemic-related stressful experiences under study were associated with TSS prevalence or incidence, especially experiences from the domains of health-related (PARP range 88.4-95.6%) and work-related stressful experiences (PARP range 76.8-86.5%). Nine stressful experiences were also associated with TSS persistence, of which having patient(s) in care who died from COVID-19 had the strongest association. This association remained significant after adjusting for co-occurring depression and anxiety. TSSs among Spanish healthcare workers active during the COVID-19 pandemic are common and associated with various pandemic-related stressful experiences. Future research should investigate if these stressful experiences represent truly traumatic experiences and carry risk for the development of post-traumatic stress disorder.